GE_GERICHTE P/9444/2019 vom 20. September 2019 - GE Cour de justice (2019)
TENTATIVE(DROIT PÉNAL);CONTRAINTE(DROIT PÉNAL);COMMANDEMENT DE PAYER;CHANTAGE;TENTATIVE(EN GÉNÉRAL) | CPP.310; CP.181; CP.156